East Asia's counterweight strategy : Asian financial cooperation and evolving international monetary order - Sohn, Injoo (UN New YorkUS, 2007)
Seeks to explain the origin, process, and prospects of East Asia's counterweight strategy in the arena of international finance, and its significant implications for global financial governance.